The Indigenous Poetry of Resistance by the Colombian Poet Fredy Chikangana: A Transitivity Systemic Analysis - Sthephanny Moncada Linares; Xin Zhi-Ying (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2021)
The emergence of Indigenous poetry to the public domain has represented a milestone in their struggle to voice their communities' past and present experiences despite the ongoing ostracizing discourses from societies as the ones residing in Indo-America. In this sense, the present paper will offer an analysis of selected poetry by the Colombian indigenous poet Fredy Chikangana in the light of the transitivity system informed by the Systemic Functional Linguistics theory to unveil their experiential meaning construal. To attain this goal, a descriptive quantitative and qualitative research method approach was applied through which the different process types, participants, and circumstances arising from the corpus were systematically identified, calculated, and analyzed. Findings indicated that among the six transitivity process types, the material processes (47%) dominated his poems, followed by the relational realizations (27%) whereas the verbal, behavioral, existential, and mental processes were relatively low altogether, representing an overall occurrence of 26%. This reveals that the author’s primary goal was to employ poetry as an agentive act of resistance that originated from the context of the situation in which his Yanakuna community has been and is immersed.